Propionic Acid Degradation by Syntrophic Bacteria During Anaerobic Biowaste Digestion - Felchner-Zwirello, Monika (Karlsruher Berichte zur Ingenieurbiologie / Institut für Ingenieurbiologie und Biotechnologie des Abwassers, Karlsruher Institut für Technologie, 2014)
Propionic acid is an important intermediate produced during anaerobic degradation of biowaste and a precursor of a large amount of methane. Its accumulation during biomethanation is however a common problem resulting in stagnation phases in biogas production. During this study, the deeper insight into the process of propionic acid degradation was intended by using modern analytical chemistry, standard microbiological approach and molecular biology for describing and explaining the problem.